2023
DOI: 10.1186/s40168-023-01622-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic exploration of coral-associated bacteria: identifying probiotic candidates to increase coral bleaching resilience in Galaxea fascicularis

Talisa Doering,
Kshitij Tandon,
Sanjida H. Topa
et al.

Abstract: Background Reef-building corals are acutely threatened by ocean warming, calling for active interventions to reduce coral bleaching and mortality. Corals associate with a wide diversity of bacteria which can influence coral health, but knowledge of specific functions that may be beneficial for corals under thermal stress is scant. Under the oxidative stress theory of coral bleaching, bacteria that scavenge reactive oxygen (ROS) or nitrogen species (RNS) are expected to enhance coral thermal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 116 publications
1
3
0
Order By: Relevance
“…The enriched enzymatic function involving the transfer of aldehyde or ketonic groups suggests a potential linkage to energy metabolism, particularly the reductive pentose phosphate cycle. This nding aligns with the ndings of Doering, et al 30 , who identi ed the complete pathway in coral-associated bacteria. Conversely, the presence of acyltransferases, associated with the phosphate acetyltransferaseacetate kinase pathway, in the seawater bacterial community indicates divergent energy-generation pathways between these two bacterial communities.…”
Section: Discussionsupporting
confidence: 91%
“…The enriched enzymatic function involving the transfer of aldehyde or ketonic groups suggests a potential linkage to energy metabolism, particularly the reductive pentose phosphate cycle. This nding aligns with the ndings of Doering, et al 30 , who identi ed the complete pathway in coral-associated bacteria. Conversely, the presence of acyltransferases, associated with the phosphate acetyltransferaseacetate kinase pathway, in the seawater bacterial community indicates divergent energy-generation pathways between these two bacterial communities.…”
Section: Discussionsupporting
confidence: 91%
“…This can be mitigated by obtaining a large number of isolates and meticulously screening and testing them for beneficial traits. Notably, all pBMC examined in this study, even those from the same genus, were distinct and demonstrated potential to contribute to the health and resilience of corals, indicating the need for continued efforts to isolate 64,171 , explore [175][176][177][178][172][173][174]177 and test 173 novel pBMC. We also highlight the discovery of prophages associated with two of the BMCs and their potential role in providing competitive advantage to coral probiotics against other bacteria.…”
Section: Red Sea Pbmc and Their Indo-pacific Ocean Counterpartsmentioning
confidence: 99%
“… 14 – 18 , 35 38 ). Recent advancements include an enhanced understanding of BMC mechanisms, the selection of probiotic strains based on genomic screening, and the exploration of other microbial therapies and bacterial experimental evolution 19 , 39 42 .…”
Section: Introductionmentioning
confidence: 99%